Konsekuensi Self Brand Connection Pada Pengguna Produk Fesyen Handmade - Adelia Widiyawati; Fatik Rahayu; Robert Kristaung (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The purpose of this research is to analyze the antecedents of electronic word of mouth (positive) among users of handmade fashion products. The questionnaire was distributed to 201 respondents via social media.  The sampling technique in this study was purposive sampling and the data were analyzed with a Structural Equation Model (SEM) using the AMOS application. The results of the research conducted are: there is a positive influence of self brand connection with brand love and there is a positive influence of brand love with positive e-WOM. This research is expected to be a useful tool for craftsmen or producers of handmade fashion products to increase positive electronic word of mouth.